Building Relationships with Community Members: Lessons Learnt from Fieldwork in Penang, Malaysia - Teresa Ong (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
As the world is rapidly chasing processes of modernisation and globalisation, many ethnic communities are perceiving global languages, such as English and Mandarin, as the language-in-demand for academic and economic purposes. This situation leads to young people shifting away from heritage languages, and as a result, heritage languages are disappearing at an alarming rate. Similar situation is taking place in Malaysia, which leads me to conduct a study examining the efforts to maintain Chinese heritage languages in Penang. Data are collected via interviews conducted with 46 participants representing three categories of macro, meso, and micro levels within the Chinese community in Penang. In this article, my goal is to share some lessons learnt from the fieldwork. Specifically, I focus on unpacking three approaches to building relationships with members of the Chinese community. They are holding small talks, being flexible to code-switching, and giving back to the community. Resulting from such relationships is that the Chinese community in Penang become more aware of heritage language maintenance.